ANALISIS AKUNTANSI PADA KEMAMPUAN PREDIKSI LABA DAN ARUS KAS DALAM MEMPREDIKSI ARUS KAS MASA DEPAN - Lutfi Aziz; Derri Mulya Vebrianto; Ica Suhazilni (JURNAL LENTERA AKUNTANSI, 2022)
This study aims to determine the ability of earning to predict future cash flow. Population in this study were companies listed on the Indonesia Stock Exchange in 2013-2020. In this study, the variabel of earning use aproxy for net income and variabel of cash flow use aproxy for operating or cash flow. The sample used in this study was banking companies listed on that Indonesia Stock Exchange in the period 2013-2020. Processing of data was done by doing classic assumption test first and then proceed to test the hypothesis. The hypothesis was tested using multiple linier regression. The result showed that earning influences in predicting future cash flow. Keywords: earning, future cash flow, banking companies